Locally Based Green Economy: The Role Of Msmes And Community Entrepreneurship In Driving Growth Sustainable Economy In Makassar City - Leny Yuliana; William Limoa; Syamsu Alam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The green economy has become a strategic framework for achieving sustainable development, particularly in developing countries where micro, small, and medium enterprises (MSMEs) play a dominant role in job creation and innovation. This study aims to analyze the role of MSMEs and community-based entrepreneurship in driving sustainable economic growth in the context of Makassar City, Indonesia. The main issue addressed in this study is how local entrepreneurial practices and community initiatives contribute to the realization of a localized green economy model. This study uses a qualitative descriptive approach with data collection through semi-structured interviews with selected MSME owners, community leaders, and local government representatives. The primary data was supplemented with secondary data in the form of policy documents and regional development reports. The analysis was conducted using thematic coding to identify recurring patterns related to environmental awareness, resource efficiency, and socioeconomic empowerme The study's findings indicate that local MSMEs have begun integrating environmentally friendly practices such as waste reduction, product recycling, and energy efficiency, despite limited institutional support and financial incentives. Furthermore, community entrepreneurship fosters social innovation by linking environmental conservation efforts with improvements in community well-being. This study concludes that the transition to a green economy in Makassar City is driven not only by government policies but also by the collective awareness and adaptive capacity of local actors. Therefore, strengthening collaboration between MSMEs, local governments, and community networks is key to accelerating inclusive and sustainable green economic growth in urban areas in Indonesia. These findings contribute to the global discourse on bottom-up strategies for achieving the Sustainable Development Goals (SDGs) through locally-based green innovation.